Why investors do not buy cheaper securities: Evidence from a natural experiment - Chan, Kalok; Wang, Baolian; Yang, Zhishu (Journal of Banking & Finance, 2019)
We examine the trading behavior of Chinese domestic investors after they were given access to the B-share market in 2001. Surprisingly, we find that only 2% of investors began buying B shares. Even among these 2%, investors were less likely to buy B shares if they had more experience in the A-share market, and vice-versa. Thus, prior market experience limits the extent to which investors respond to A/B-share premiums and liquidity and lowers their performance. Our findings cannot be explained by government intervention, investor heterogeneity, foreign currency constraint, A/B-share liquidity or speculation differentials, or information advantage.